Highly sensitive early-onset Alzheimer's disease: a case report - Rubiño-Díaz, José Ángel; Zapata-Moreno, Melania (Frontiers in Psychology, 2025)
BackgroundEarly-onset Alzheimer's disease (EOAD) is an atypical syndrome that can be confused with other neurodegenerative diseases. This disease presents before the age of 65, with symptoms that generally affect executive functions, praxis, and visuoperceptual abilities, as opposed to episodic memory. Highly sensitive individuals present the temperament trait of sensory processing sensitivity, which is characterized by a differential susceptibility compared to other individuals. Neuropsychological evaluation should involve a holistic and integrative person-centered care approach for optimal treatment and disease progression.Case summaryA highly sensitive 54-year-old individual was diagnosed with EOAD at age 47 in 2017. Neuropsychological follow-up was conducted for 6 years. Initial neuropsychological testing revealed a cognitive pattern with impairments in executive functions, attention, and visual perception, the advancement of which led to a progressive deterioration in daily, occupational, and social functioning. During this period, he received psychotherapy from a psychologist specializing in neuropsychology and high sensitivity, using a holistic and integrative approach. Initially, sessions were held twice a week throughout the first year of consultation and, subsequently, continued at the patient's home and in his usual context, using a completely ecological perspective and consisting of person-centered care. In 2022, the patient, aged 59, was admitted to a nursing home. This situation, outside his usual environment, without autobiographical references and his own life story, led to accelerated deterioration, with the patient ultimately dying at age 60, in 2023.ConclusionThe patient with highly sensitive EOAD was followed for 6 years by a psychologist specializing in neuropsychology and high sensitivity. Neuropsychological intervention was maintained with a holistic and integrative person-centered approach using the unmet needs model to address cognitive, psychological, and functional levels. Follow-up with this approach could be key to slowing the disease and ensuring patient satisfaction throughout the entire progression of the illness. Greater visibility into unusual cases like this will enable psychology professionals to be vigilant for timely differential and diagnostic testing, which will significantly impact the treatment and progression of the illness, ultimately influencing quality of life and well-being through an optimal neuropsychological approach.